The Effectiveness of Health, Educational, and Economic Awareness Programs to Reduce the Negative Effects of Internet Addiction on the Academic Achievement of Primary School Children - Fatma Salah Eldin Kassem Mohamed; Abdalmajeed Selmi Arrooqi; Atallah Alenezi; Mona Ahmed Elsemary; Manal Saleh Moustafa Saleh (Qubahan Academic Journal)
Internet addiction negatively affects the health of children in the primary stage, which is reflected in their academic achievement negatively, and also affects Internet addiction on the economic level of these children's families. Therefore, it was necessary to apply a health, educational, and economic awareness program to reduce the negative effects of Internet addiction on the academic achievement of primary school children. Aim To investigate effectiveness of health, educational, and economic awareness program to reduce the negative effect of Internet addiction on the academic achievement of primary school children at Shaqra City. Research Design Quasi-experimental, included parents of primary schools’ children at Shaqra used to fulfill the aim of the present study, The study settings using a multistage random sampling technique. Accordingly, the carry out in Shaqra primary schools, a governmental school. 100 parents (mother or father) of primary school children’s participants. Tools of gathering data: Questionnaire on the impact of Internet addiction on the academic achievement of primary school children, health, educational, and economic awareness program to reduce the negative effects of Internet addiction on the academic achievement of primary school children, Statistical methods (T.test and Likert quintuple scale) have been used to analyze the data. Results was the effectiveness of the awareness program in reducing the negative effects of Internet addiction among primary school children, The results showed a significant impact of the program, with significant statistical differences in post-test measurements compared to pre-test measurements. The study recommends applying the awareness program to more schools and different age groups, and increasing the duration of the program for a period of not less than six months. limitations encountered during the study; the short duration of the program was one of the limitations faced by the current study.